Analisis Faktor-Faktor yang Mempengaruhi Indeks Pembangunan Manusia di Provinsi Riau Tahun 2021-2024 - Fradani, Faisal Agymnastiar Rahmad; Aziza, Nadifa Nur; Wieligmans, Getruida Slvia Dewi; Monika, Ketalat; Wijayanti, Heni Puri; Rahajeng, Anggi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to examine the socioeconomic factors influencing the Human Development Index (HDI) in Riau Province during the 2021–2024 period. A quantitative method was employed through a panel data regression approach on 12 districts/cities, combined with spatial analysis using ArcGIS software to map geographical disparities in HDI. The independent variables analyzed include the open unemployment rate (OUR), poverty rate, population size, average years of schooling, life expectancy, economic growth, and road infrastructure. The estimation results indicate that the poverty rate has a significant negative effect on HDI, while population size, average years of schooling, and life expectancy have significant positive effects. Meanwhile, the open unemployment rate, economic growth, and road infrastructure do not show significant effects. The spatial mapping reveals human development disparities across Riau Province, with the highest HDI levels found in urban areas and the lowest in coastal regions. These findings highlight the importance of more inclusive development policies to enhance access to education, healthcare services, and equitable infrastructure distribution.